Life Cycle Assessment of Phosphogypsum as Filler Material for Coal Fly Ash-Based Geopolymer - Paulo, Jacob Louies Rohi W.; Pablo, Michelle Airah N.; Pocaan, Joshua P.; Promentilla, Michael Angelo B.; Beltran, Arnel B.; Madlangbayan, Marish S.; Palattao, Botvinnik L.; Ramirez, Jennyvi D.; Tabelin, Carlito B.; Resabal, Vannie Joy T.; Orbecido, Aileen H.; Tapia, John Frederick D.; Pausta, Carla Mae J. (Salehan Institute of Higher Education, 2025)
The global accumulation of phosphogypsum (PG), with annual generation exceeding 175 Mt/year, presents significant environmental challenges. While studies have demonstrated PG's potential as a filler material in geopolymer composite, comprehensive environmental impact assessments of such valorization approaches remain limited. This study presents the first comparative life cycle assessment (LCA) of acid- and alkali-activated PG-CFA geopolymers in the context of sustainable industrial waste management. Geopolymer technology can eliminate the need for traditional landfilling of PG in coastal areas and, therefore, reduce their negative environmental impacts. LCA was conducted to assess the impacts of repurposing 1kg functional unit of PG as geopolymer precursors coupled with acid- and alkali-based activators compared to the current disposal practices of these solid wastes. The inventory was modeled after a phosphoric acid plant using the wet dihydrate process, a coal-fired power plant, and a laboratory-scale coal fly ash-phosphogypsum geopolymer (FAPG) synthesis upscaled for industrial application. The most number of environmental benefits was observed for acid FAPG particularly via reductions in CO2-eq emissions by 40%, 90% in energy consumption, and 36% in mineral resource extraction. Alkali FAPG excelled in water acidification and scarcity by 60% and it could outperform acid FAPG environmentally via sensitivity analysis under a similar formulation blend. Further research can focus on optimizing FAPG formulation, finding alternatives for the acid and alkali activators, and reviewing industrial standards for widespread FAPG applications. These results imply the potential of integrating FAPG manufacturing in PG- and CFA-generating industries to emulate a circular economy.